FOR THE TREATMENT OF POST-TRAUMATIC STRESS DISORDER, VIRTUAL REALITY EXPOSURE - Prem Lata Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Research indicates an interlink between traumatic experiences and criminal behaviour (Ardino, 2011; Foy, Furrow & McManus, 2011; Weeks & Widom, 1998, 1989) revealing that offenders present a higher prevalence of Post-traumatic Stress Disorder (PTSD; APA, 1994) and associated symptoms when compared with the general population (Wright, Borrill, Teers & Cassidy, 2006). (Wright, Borrill, Teers & Cassidy, 2006). Available research, however, seldom give evidence regarding particular pathways that relate trauma and PTSD to criminal activity. This topic cluster of articles Offending behaviour: the role of trauma and PTSD’’ intends to study such trajectories and post-traumatic processes in offenders. Victims of violence are prone to a constellation of consequences including dissociation, drug misuse, depression, and PTSD (Foa, Ehlers, Clark, Tolin & Orsillo, 1999; Roth, Newman, Pelcovitz, Van der Kolk & Mandel, 1997). (Foa, Ehlers, Clark, Tolin & Orsillo, 1999; Roth, Newman, Pelcovitz, Van der Kolk & Mandel, 1997). Chronic and extended exposure to violence may grow into a dysfunctional habit conducted in both familial and community contexts generating ‘‘a connection between experiences of violence as victims and subsequent experiences of violence as a perpetrator’’ (Garbarino, 2002) via which trauma continuously appears to be the linking element for various forms of violence*endured or inflicted (Ardino, 2011). (Ardino, 2011).